Introducing PEGI: a usability process for the practical evaluation of Geographic Information - Brown, Michael; Sharples, Sarah; Harding, Jenny (Elsevier, 2013)
As the use of Geographic Information (GI) is becoming more widespread, the usability of GI is being recognised as an important issue. However, exploring the usability of information products brings with it a range of problems that are not easily handled by traditional user centred design methods. This paper describes the Practical Evaluation of Geographic Information (PEGI) process, which consists of a series of usability research methods that have been modified for use with GI. Two case studies are also presented, describing the application of PEGI within a commercial product development process. The advantages and disadvantages of the PEGI process are discussed as well as plans for future research in this area. The potential value of this approach is also described in terms of Cost-Benefit, concluding that a £3,000 evaluation process could help produce benefits of over £40,000 a year in cost savings and increased sales.